Analysis Of The Consumption Behaviour Of Blood Supplement Tablets Among Female Students At Stikes Panakkukang - Lende, Ranisri; Mikawati; Muaningsih; Suriyani; Pratiwi, Rizky (Universitas STRADA Indonesia, 2024)
Blood supplement tablets are very important in consumption for female students as iron supplementation and to avoid various impacts, one of which is anaemia. Lack of consumption of blood supplement tablets can cause symptoms such as weakness, fatigue, lethargy, fatigue, inattentiveness, dizziness, and decreased learning concentration. To know the knowledge, attitude and behaviour of female students in consuming blood supplement tablets in female students at STIKES Panakkukang.Research. Analytical design with a retrospective approach. The research sample was 217 respondents with the sampling technique was probability sampling, namely Proportionate stratified random sampling. The instrument used a questionnaire in the form of google form. Results: There is a relationship between knowledge, attitudes and behaviour of female students in consuming blood tablets in female students at STIKES Panakkukang with a p value of 0.001 and 0.005 where the p value is <0.05 so that it is concluded that Ho is rejected and Ha is accepted. Good knowledge and positive attitudes of female students related to blood tablets have a relationship with good behaviour of female students in consuming blood tablets. Especially for female students in higher education to improve the behaviour of consuming blood tablets and self-awareness of the importance of consuming blood tablets.